2010
DOI: 10.4269/ajtmh.2010.09-0342
|View full text |Cite
|
Sign up to set email alerts
|

Association between Mannose-Binding Lectin Polymorphisms and Wuchereria bancrofti Infection in Two Communities in North-Eastern Tanzania

Abstract: Abstract. The association between selected mannose-binding lectin (MBL) genotype polymorphisms and Wuchereria bancrofti infection status was assessed among individuals whose infection status had been monitored for three decades. Blood samples were collected in 2006 and examined for polymorphisms in the mbl-2 gene and for W. bancrofti -specific circulating filarial antigen (CFA) status. Logistic regression analysis showed a significant association between MBL genotype and CFA status, with low-expression MBL gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 29 publications
1
21
0
1
Order By: Relevance
“…These data suggest that higher levels of CIC augment complement system activation in asymptomatic infected patients with filariasis, a response likely to reflect a host protective strategy because the MBL pathway has been associated with resistance to filarial infection. [22][23][24] In terms of pathogenesis of lymphatic disease in LF, there is growing evidence to suggest that recurrent bacterial infections are an essential cofactor in development of lymphedema and its progression to elephantiasis. 3 The complement system is a fundamental element of the normal host defense against infection.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that higher levels of CIC augment complement system activation in asymptomatic infected patients with filariasis, a response likely to reflect a host protective strategy because the MBL pathway has been associated with resistance to filarial infection. [22][23][24] In terms of pathogenesis of lymphatic disease in LF, there is growing evidence to suggest that recurrent bacterial infections are an essential cofactor in development of lymphedema and its progression to elephantiasis. 3 The complement system is a fundamental element of the normal host defense against infection.…”
Section: Discussionmentioning
confidence: 99%
“…These have shown significant results at CHIT1 [90], MBL2 [90,91], TGFB1 [92], TLR2 [93] and CTLA4 [94] for susceptibility to infection, at VEGFA for progression to hydrocele [95], and at TNFR2 and ET1 for progression to elephantiasis as opposed to hydrocele [96].…”
Section: Filariasis Lymphatic Filariasismentioning
confidence: 91%
“…Thus, chitotriosidase I and mannose-binding lectin 2 (MBL2) polymorphisms were shown to be associated with increased susceptibility to filarial infections in one study (135), although this could not be confirmed in another geographical area (138). Another study revealed a significant association between MBL genotypes and the presence of infection in Africa (139). Studies have also implicated TLR2 polymorphisms in susceptibility to infection (140).…”
Section: Pathogenesis Of Lymphedema – Role Of Adaptive Immunitymentioning
confidence: 99%